Elevação da excelência do suco de uva: revelando o impacto da aplicação foliar pré-colheita de extrato de levedura nos parâmetros de qualidade - Moro, Laís [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
This research investigates the effects of foliar application of selected inactivated yeast on juice grape varieties ('Isabel,' 'Isabel Precoce,' 'Ives,' 'Concord,' and 'BRS Violeta') cultivated at the Centro Avançado de Pesquisa e Desenvolvimento de Frutas of the Instituto Agronômico (IAC), São Paulo, Brazil. The vines were trained on vertical shoot-positioning (VSP) and overhead trellis systems (TOS), with a randomized block design applied in four replicates. The study assessed plant productivity and the physical characteristics of grape clusters and berries. Additionally, grape juice extracted from these varieties in the 2022 season underwent sensory analysis in a laboratory at São Paulo State University (UNESP), with approval from the Research Ethics Committee of the Botucatu School of Medicine (FMB-UNESP, CAAE: 63416122.0.0000.5411). Stilbene compounds were quantified post-processing using high-performance liquid chromatography (HPLC) with a diode array detector (DAD). Conducted over three years, the study found no significant impact of yeast extract application on vine productivity or berry physicochemical parameters. However, different training systems responded uniquely to the treatment, with VSP showing the most notable effects in stilbene content. Among the varieties, ‘Ives’ and ‘BRS Violeta’ received the highest sensory scores, while ‘Concord’ received the lowest overall impression scores. Results varied by grape variety and training system, emphasizing the importance of varietal selection and suggesting the potential for creating blends that highlight each variety's strengths. The initial part of the study is freely available at Discover Food journal within the title: Exploring grape juice volatile compounds after inactive yeast extract foliar treatment using SPME and GC–MS.
Elevating grape juice excellence: unveiling the impact of pre-harvest yeast extract foliar application on quality parameters
Keywords: Viticultura; Vitis labrusca; Grape juice; Biofortification